Influence of electrolyte structural evolution on battery applications: Cationic aggregation from dilute to high concentration. Issue 1 (17th January 2022) - Hu, Jiangtao; Ji, Yuchen; Zheng, Guorui; Huang, Weiyuan; Lin, Yuan; Yang, Luyi; Pan, Feng
Abstract: In the context of the rapid expansion of the electric vehicle market, the request for high‐energy‐density lithium‐ion batteries (LIBs) has steadily increased, hence the demand for highly stable electrolytes. Over the past years, efforts have been devoted to the improvement of electrolyte materials. As a benchmarking breakthrough, the achievement of high concentration electrolyte (HCE) can be attributed to the altered cationic aggregation (i.e., cation‐solvent and cation‐anion coordination environment), which offers technical superiority over the widely applied conventional dilute electrolytes. More recently, based on the understanding of the dilute electrolyte and HCE, the concept of localized HCE (LHCE) has been proposed and extensively investigated. All these findings reveal a roadmap of electrolyte optimization for high‐performance LIBs via coordination structure regulation. Through elucidating the correlation of structure evolution therein and its critical effects on battery performance, this review aims to establish the design principle of electrolytes based on their structures other than component studies and thereby accelerate the development of high‐performance electrolytes. Abstract : A new electrolyte design route is proposed by taking cationic aggregation structure into consideration based on the understanding of the correlation between electrolyte structure evolution and its effects on battery performance. This review will also summary the characterization techniques of electrolyte structures for better understanding.